Changes in motivation while working with the hypermedia learning program RACE - Thielke, S.; Rockmann, U.; Seyda, M. (International Journal of Computer Science in Sport, 2003)
In most experiments only motives like dispositions are measured (trait measurement) although the classic psychology of motivation (Atkinson, 1957; Heckhausen, 1989) assumes that behavior is the result of interaction between situational and personal factors. Rheinberg et al. (2001) developed a four-factor questionnaire (QCM) to record the result of this interaction as a state of current learning motivation. The four factors are fear, probability of success, interest, and challenge. We report an experiment that shows that the type of medium has an effect on specific motivational factors but not on performance. In a group comparison design, one group (N=8) worked with paper learning cards and one (N=12) worked with the hypermedia environment RACE. Before and after the acquisition phase, performance was tested. A QCM was given after subjects had been given instructions but directly before the acquisition phase and again 30 min. after the acquisition phase. The results show no specific effect on the current motivation based on the type of media (p =.397). Nor could any correlation between motivation and performance be detected. We found that subjects working with RACE show higher scores in factors like interest (p < .05) and challenge (p < .01) than subjects working with cards.